2021
DOI: 10.3389/fphar.2021.705421
|View full text |Cite
|
Sign up to set email alerts
|

The Prostacyclin Analogue, Treprostinil, Used in the Treatment of Pulmonary Arterial Hypertension, is a Potent Antagonist of TREK-1 and TREK-2 Potassium Channels

Abstract: Pulmonary arterial hypertension (PAH) is an aggressive vascular remodeling disease that carries a high morbidity and mortality rate. Treprostinil (Remodulin) is a stable prostacyclin analogue with potent vasodilatory and anti-proliferative activity, approved by the FDA and WHO as a treatment for PAH. A limitation of this therapy is the severe subcutaneous site pain and other forms of pain experienced by some patients, which can lead to significant non-compliance. TWIK-related potassium channels (TREK-1 and TRE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 69 publications
(142 reference statements)
0
1
0
Order By: Relevance
“…KCNK2 channels are expected to become an interactive target for the treatment of depression, cerebral ischemia, general anesthesia, analgesics, ventricular tachycardia, and cancer ( 35 ). A recent study reported that treprostinil (prostacyclin analogue), which is used for PAH patients, inhibited KCNK2 channels ( 59 ). The effects of treprostinil in PAH patients may be partially mediated by its inhibition of KCNK2 channels.…”
Section: Discussionmentioning
confidence: 99%
“…KCNK2 channels are expected to become an interactive target for the treatment of depression, cerebral ischemia, general anesthesia, analgesics, ventricular tachycardia, and cancer ( 35 ). A recent study reported that treprostinil (prostacyclin analogue), which is used for PAH patients, inhibited KCNK2 channels ( 59 ). The effects of treprostinil in PAH patients may be partially mediated by its inhibition of KCNK2 channels.…”
Section: Discussionmentioning
confidence: 99%